2016
DOI: 10.1177/0194599816644738
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Paralysis after Esophagectomy for Carcinoma

Abstract: Cervical approaches are associated with increased VFP in patients undergoing esophagectomy for malignancy. When cervical approaches and mobilization are required, the inclusion of an experienced cervical surgeon to identify the RLN may improve the rate of postoperative VFP. Patients with VFP after esophagectomy experience significantly more morbidity. Due to the potential delay in diagnosis and treatment of postoperative VFP, routine assessment of inpatient vocal fold function may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…These findings were confirmed in more recent studies, all demonstrating an increase in pulmonary complications after esophagectomy complicated by RLNP (9,10,20,24). Similarly to our results, Koyanagi et al (10) found an association between RLNP and prolonged hospital stay.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings were confirmed in more recent studies, all demonstrating an increase in pulmonary complications after esophagectomy complicated by RLNP (9,10,20,24). Similarly to our results, Koyanagi et al (10) found an association between RLNP and prolonged hospital stay.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study regarding short-term complications after RLN injury during esophagectomy are in line with current literature (9,10,20,23,24). The first study published on this topic found higher rates of pulmonary complications after RLNP, leading to a higher reintubation rate, and consequently a prolonged ventilation time and longer ICU stay (23).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We mostly attribute this to the small sample size in this study. As VFP after esophagectomy occurs only in around 24% of patients, we were not able to discern this statistically with only a few patients in each group [21]. In our study population, surgery was performed for the treatment of EC and not for the treatment of ERF.…”
Section: Discussionmentioning
confidence: 86%